El proceso administrativo y el posicionamiento en el restaurant La Patrona Snack & Parrillas Iquitos 2020 - Paucar Barbaran, Pablo Cesar (2021)
The general objective of this research work is to determine the relationship that exists between the administrative process and positioning in the Restaurant La Patrona Snack & Parrillas, Iquitos-2020. The method used is of a Quantitative-Descriptive nature, because the administrative process and positioning were evaluated, this is how it is concluded with the administrative process study variable, it is observed that 52.5% are "in agreement" with the comfort in care that is offered in the restaurant, also indicate that the best option to continue interacting and communicating are social networks as shown by the survey with 87.5%, customers consider that the staff is trained in care (75%), the The price you pay for your food is fair to the level of satisfaction you perceive and that you pay with pleasure. Regarding the positioning study variable, 75% of customers indicate what defines their purchase decision is the characteristic of the service who offers it and that they feel that the restaurant is for all the socioeconomic extracts (75%) without discrimination by the purchasing power of the client. Clients indicate that they interact through the networks recommending other users to visit the business as shown by the results obtained in the survey (75%), they are "Agree". With which hypothesis 1 (H1) is demonstrated: There is a relationship between the positioning and the administrative process in the Restaurant La Patrona Snack & Parrillas, Iquitos 2020.